Cross‐cultural invariance of NPI‐13: Entitlement as culturally specific, leadership and grandiosity as culturally universal. (15th April 2018) - Żemojtel‐Piotrowska, Magdalena; Piotrowski, Jarosław; Rogoza, Radosław; Baran, Tomasz; Hitokoto, Hidefumi; Maltby, John
Abstract : The current study explores the problem with the lack of measurement invariance for the Narcissistic Personality Inventory (NPI) by addressing two issues: conceptual heterogeneity of narcissism and methodological issues related to the binary character of data. We examine the measurement invariance of the 13‐item version of the NPI in three populations in Japan, Poland and the UK. Analyses revealed that leadership/authority and grandiose exhibitionism dimensions of the NPI were cross‐culturally invariant, while entitlement/exploitativeness was culturally specific. Therefore, we proposed NPI‐9 as indicating scalar invariance, and we examined the pattern of correlations between NPI‐9 and other variables across three countries. The results suggest that NPI‐9 is valid brief scale measuring general levels of narcissism in cross‐cultural studies, while the NPI‐13 remains suitable for research within specific countries.